\(H_v\)-Structures and the bar in questionnaires - Nikolaidou, Pipina; Vougiouklis, Thomas (Italian Journal of Pure and Applied Mathematics, 2012)
The class of hyperstructures called Hv-structures has been studied from several aspects as well as in connection with many other topics of mathematics. Here we present applications obtained from social sciences mainly the ones used questionnaires. Moreover we improve the procedure of the ¯lling the questionnaires, using the bar instead of Likert scale, on computers where we write down automatically the results so they are ready for research.